Bacterial pathogens, virulence mechanism and host defence in marine macroalgae. (21st October 2013) - Egan, Suhelen; Fernandes, Neil Daniel; Kumar, Vipra; Gardiner, Melissa; Thomas, Torsten
Summary Macroalgae are important ecosystem engineers in temperate marine waters. The function of macroalgae is intimately linked to the composition and structure of their epibiotic bacterial, communities, and evidence has emerged that bacteria can also have a negative impact on their host by causing disease. A few examples exist where bacteria have been unambiguously linked to macroalgal disease, however in many cases, pathogenicity has not been clearly separated from saprophytic behaviour or secondary colonization after disease initiation. Nevertheless, pathogenic pressure by bacteria might be substantial, as macroalgae have evolved a range of innate and induced defence mechanism that have the potential to control bacterial attacks. The presence and abundance of virulence factors in marine bacteria, which have not previously been recognized as pathogens, also represents an underappreciated, opportunistic potential for disease. Given that virulence expression in opportunistic pathogens is often dependent on environmental conditions, we predict that current and future anthropogenic changes in the marine environment will lead to an increase in the occurrence of macroalgal disease. This review highlights important areas of research that require future attention to understand the link between environmental change, opportunistic pathogens and macroalgal health in the world's oceans.